Study of the Functional, Physical and Sensory Properties of Wheat Flour, Orange Peel Powder and Manufactured Biscuits (Eurasian Medical Research Periodical, 2022)
This study was conducted in the laboratories of the Department of Food Sciences - College of Agriculture - Tikrit University. During the period from August 2021 to January 2022. With the aim of evaluating the functional properties of flour and orange peel powder, a biscuit was also produced with orange peel powder added in rates of 8, 16, 24 and 32%, and evaluation of the physical and sensory properties of the produced biscuits. The experiment was carried out according to a completely randomized design, and the results were as follows: Orange peel powder was distinguished by the highest values significantly compared to wheat flour in most of the functional properties and achieved averages of 9.89 ml water/gm, 5.44 gm water/gm and 1.13 gm oil/gm for the characteristics of swelling ability, water binding capacity and oil binding capacity, respectively. The standard biscuit sample was significantly superior in most of the physical properties and achieved averages of 6.11, 10.43 and 0.45 cm, followed by the 32% biscuits treatment with orange peel powder with averages of 4.57, 15.88 and 0.43 cm for the characteristics of diameter, expansion rate and thickness, respectively. The results of the sensory evaluation showed that the standard sample was significantly superior to all sensory traits except for the color trait, in which the biscuit treatment 8% was superior, which came in the second order significantly, for all traits, while the treatment of biscuits 32% orange peel powder recorded the lowest averages significantly in all traits